2020
DOI: 10.1128/mbio.00217-20
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics and Community Composition Influence Gas Production of the Human Gut Microbiota

Abstract: Prebiotics confer benefits to human health, often by promoting the growth of gut bacteria that produce metabolites valuable to the human body, such as short-chain fatty acids (SCFAs). While prebiotic selection has strongly focused on maximizing the production of SCFAs, less attention has been paid to gases, a by-product of SCFA production that also has physiological effects on the human body. Here, we investigate how the content and volume of gas production by human gut microbiota are affected by the chemical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
3
19
0
2
Order By: Relevance
“…Hydrogenase activity can be predicted based on primary sequence ( Søndergaard et al, 2016 ). The HydDB database has been widely utilized to classify hydrogenases ( Dong, 2020 ; Mei, 2020 ; Panwar, 2020 ; Park et al, 2020 ; Picone et al, 2020 ; Stairs et al, 2020 ; Wong, 2020 ; Yu et al, 2020 ). We confirmed the reliability of gene annotations in the HydDB database using a simulated metagenomic dataset of hydrogenase-containing and hydrogenase-free genomes (see Materials and methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenase activity can be predicted based on primary sequence ( Søndergaard et al, 2016 ). The HydDB database has been widely utilized to classify hydrogenases ( Dong, 2020 ; Mei, 2020 ; Panwar, 2020 ; Park et al, 2020 ; Picone et al, 2020 ; Stairs et al, 2020 ; Wong, 2020 ; Yu et al, 2020 ). We confirmed the reliability of gene annotations in the HydDB database using a simulated metagenomic dataset of hydrogenase-containing and hydrogenase-free genomes (see Materials and methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation of carbohydrates by human gut microbiota usually produces gases. Production of H 2 is often necessary for the cycling of NAD + /NADH during fermentation, and CO 2 is released whenever decarboxylation occurs [ 31 ]. C3G did not have sufficient carbohydrates for the fermentation by gut microbiota; therefore, the gas volume of C group was very low ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…C3G did not have sufficient carbohydrates for the fermentation by gut microbiota; therefore, the gas volume of C group was very low ( Figure 2 A). The chemical composition of the prebiotics and the composition of the microbiota are related to the amount of produced gas during fermentation [ 31 ]. A previous study showed that inulin has a higher potential to produce H 2 than pectin during in vitro fermentation, due to its composition, and its total gas production was significantly higher than pectin [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, large-scale quantitative validation experiments are necessary for testing these models, where in vivo microbial growth rates and metabolite fluxes are measured to identify which metabolic processes are captured well by the model and which ones are not. Ex vivo growth experiments, where fecal samples are incubated under anaerobic conditions with a wide array of dietary metabolites, represent a promising high-throughput approach to observing gut microbial community metabolic output in the absence of the host 161 , 162 . Similarly, humanized gnotobiotic mice may prove to be a key tool in improving metagenome-scale metabolic models, by providing a well-controlled in vivo experimental model to optimize metabolic predictions.…”
Section: Future Directions: From Diagnosis To Personalizationmentioning
confidence: 99%